RE-Examining Berman's Parametrization Of The Hubble Parameter In The Context Of Late-Time Acceleration - Mishra, K. R.; Pacif, S. K. J.; Kumar, R.
In this paper, we have revisited the Berman's idea of the variation of Hubble parameter. While previously explored in the context of  -varying cosmologies, where scale factor variations yield linear universe expansion, this parametrization has undergone extensive scrutiny. Our investigation, however, explores into its implications in the context of late-time cosmic acceleration, within the framework of classical general relativity, adopting the Friedmann-Lemaître-Robertson-Walker (FLRW) spacetime as our background metric. Our analysis offers a precise solution to Einstein's field equations (EFEs) in a model-independent way, affording a thorough assessment of both geometrical and physical model parameters. Additionally, this study supplements its findings with graphical representations of the evolving cosmological parameters across flat, closed, and open universe scenarios, all subject to constraints derived from the model parameters. In synthesizing these results, we shed light on the intricate interplay between cosmic acceleration, dark energy, and the parametrization of the Hubble parameter, thereby providing valuable insights into the fundamental mechanics of our universe.
Keywords: Astrophysics